2015
DOI: 10.1007/s10534-015-9857-5
|View full text |Cite
|
Sign up to set email alerts
|

Selenium as an antidote in the treatment of mercury intoxication

Abstract: Selenium (Se) is an essential trace element for humans. It is found in the enzyme glutathione peroxidase. This enzyme protects the organism against certain types of damage. Some data suggest that Se plays a role in the body's metabolism of mercury (Hg). Selenium has in some studies been found to reduce the toxicity of Hg salts. Selenium and Hg bind in the body to each other. It is not totally clear what impact the amount of Se has in the human body on the metabolism and toxicity of prolonged Hg exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In addition, Hg may also bind to selenium (Se). Several studies in humans showed that administration of Se to individuals exposed to Hg reduces the overall intoxication induced by Hg (Bjorklund 2015; Chen et al 2006). It is not clear if Hg-Se complexes are transportable forms of Hg.…”
Section: Aging and Exposure To Mercurymentioning
confidence: 99%
“…In addition, Hg may also bind to selenium (Se). Several studies in humans showed that administration of Se to individuals exposed to Hg reduces the overall intoxication induced by Hg (Bjorklund 2015; Chen et al 2006). It is not clear if Hg-Se complexes are transportable forms of Hg.…”
Section: Aging and Exposure To Mercurymentioning
confidence: 99%
“…10 Mercury toxicity is reduced by selenium, an essential nutrient present in seafood that has high binding affinity to mercury. 11 In this study, we examined the associations of dementia neuropathologies with dietary n-3 fatty acids and with brain levels of mercury and selenium.…”
mentioning
confidence: 99%
“…Selenium has been found to be a very good antidote for mercury poisoning in animal experiments [154][155][156]. However, selenium intake is less than optimal for much of the world population [154,155].…”
Section: Selenium and Selenoproteinsmentioning
confidence: 99%
“…Selenium has been found to be a very good antidote for mercury poisoning in animal experiments [154][155][156]. However, selenium intake is less than optimal for much of the world population [154,155]. When the dietary selenium intake is less than optimal, seleniumantagonistic toxic metals, such as mercury, cadmium, and silver, bind selenium in a biologically inert form as heavily soluble selenides.…”
Section: Selenium and Selenoproteinsmentioning
confidence: 99%